Electron Acceptor-Driven Solid Electrolyte Interphases with Elevated LiF Content for 4.7 V Lithium Metal Batteries - Yongbiao Mu; Zifan Liao; Youqi Chu; Qing Zhang; Lingfeng Zou; Lin Yang; Yitian Feng; Haixiang Ren; Meisheng Han; Lin Zeng (Nano-Micro Letters)
Highlights A tris(pentafluorophenyl)borane additive as an electron acceptor is incorporated into an ethyl methyl carbonate/fluoroethylene carbonate/lithium nitrate electrolyte. This approach effectively engineers durable dual interfaces on both lithium metal anode and LiNi0.8Mn0.1Co0.1O2 (NCM811) cathode, which mitigates dendritic growth and enhances cathode stability. The additive-driven strategy enables lithium metal batteries to operate at ultra-high voltage up to 4.7 V and high mass loading of 14.0 mg cm−2 for NCM811 cathode, thus resulting in exceptional cycling performance.